Hybrid mesoporous electrodes evidence CISS effect on water oxidation - Vensaus, Priscila (2024)
Controlling product selectivity is essential for improving the efficiency of multi-product reactions. Electrochemical water oxidation is a reaction of main importance in different applications, e.g., renewable energy schemes and environmental protection, where H2O2 and O2 are the two principal products. In this Communication, the product selectivity of electrochemical water oxidation was controlled by making use of the chiral induced spin selectivity (CISS) effect at mesoporous-TiO2 on the molecule-modified Au substrate. Our results show a decrease in H2O2 formation when using chiral hetero-helicene molecules adsorbed on the Au substrate. We propose a mechanism for this kinetic effect based on the onset of CISS-induced spin polarization on the Au-helicene chiral interface. We also present a new tunable substrate to investigate the CISS mechanism.